Development Of Educational Neuroscience In Primary Schools - Kodiran (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2023)
This article aims to explain the implementation of educational neuroscience research results in elementary schools. The method for writing this article is literature study by exploring various scientific papers related to this topic. The results of the author's study conclude that educational neuroscience is a field of neuroscience study that focuses on studying educational concepts in a transdisciplinary manner from a neuroscience perspective. The results of educational neuroscience research prove that the structure of the nervous system underlies human actions, including aspects of cognition, affection and psychomotor. Implementation of neuroscience research results in basic education involves neuroscience, cognitive neuroscience, psychology, educational theory, and learning practices. The concept of learning from a neuroscience perspective is learning that empowers the brain's abilities by creating a learning environment that is challenging, fun, meaningful, and encourages students to be active. Thus, educational neuroscience is a future educational model that is important for elementary school teachers to know.